Association between family functions and antenatal depression symptoms: a cross-sectional study among pregnant women in urban communities of Hengyang city, China. Issue 8 (5th August 2020) - Zheng, Baohua; Yu, Yunhan; Zhu, Xidi; Hu, Zhao; Zhou, Wensu; Yin, Shilin; Xu, Huilan
Abstract : Objective: To explore the prevalence of depressive symptoms among women in late pregnancy, and assess mediating effect of self-efficacy in the association between family functions and the antenatal depressive symptoms. Design: Community-based, cross-sectional study was conducted among women during the third trimester of pregnancy. Setting: This study was conducted among pregnant women registered at community health service centres of urban Hengyang City, China from July to October 2019. Participants: 813 people were selected from 14 communities by multi-staged cluster random sampling method. Main outcome measures: The Family Adaptation Partnership Growth Affection and Resolve Index, the General Self-efficacy Scale and Patient Health Questionnaire were used to access family functions, self-efficacy and antenatal depression symptoms, respectively. Results: In this study, 9.2% pregnant women reported the symptoms of antenatal depression (95 CI% 7.2% to 11.2%). After adjustment, the results showed that severe family dysfunction (adjusted OR, AOR 3.67; 95% CI 1.88 to 7.14) and low level of self-efficacy (AOR 3.16; 95% CI 1.37 to 7.27) were associated with antenatal depressive symptoms (p < 0.05). Furthermore, self-efficacy level partially mediated the association between family functions and antenatal depressive symptoms(β=−0.05, 95% CI −0.07 to −0.03, p < 0.05) and the mediating effect accounted for 17.09% of the total effect. Conclusions: This study reported 9.2% positive rates of antenatal depression symptoms among women in the third trimester of pregnancy in Hengyang city, China. The mediating effect of self-efficacy on the association between family functions and antenatal depression symptoms among women in the third trimester of pregnancy was found in this study, which provide a theoretical basis to maternal and child health personnel to identify high-risk pregnant women and take targeted intervention for them.